2017
DOI: 10.3758/s13428-017-0892-8
|View full text |Cite|
|
Sign up to set email alerts
|

The Montreal Protocol for Identification of Amusia

Abstract: The Montreal Battery for the Evaluation of Amusia (MBEA; Peretz, Champod, & Hyde Annals of the New York Academy of Sciences, 999, 58-75, 2003) is an empirically grounded quantitative tool that is widely used to identify individuals with congenital amusia. The use of such a standardized measure ensures that the individuals tested will conform to a specific neuropsychological profile, allowing for comparisons across studies and research groups. Recently, a number of researchers have published credible critiques … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 75 publications
(67 reference statements)
0
43
0
1
Order By: Relevance
“…In the musical domain, previous studies have observed gray matter volume differences between expert, amateur, and non-expert musicians; and expert or non-expert dancers (Gaser and Schlaug, 2003; Nigmatullina et al, 2015; Sluming et al, 2002). Furthermore, VBM studies (Hyde et al, 2006; Mandell et al, 2007) have examined co-variation of gray matter volume with participant performance on a musical assessment test (Peretz et al, 2003) to identify candidate brain regions that are related to the phenotypic expression of congenital amusia or tone-deafness (a pitch perception deficit, Vuvan et al, 2017). …”
Section: Introductionmentioning
confidence: 99%
“…In the musical domain, previous studies have observed gray matter volume differences between expert, amateur, and non-expert musicians; and expert or non-expert dancers (Gaser and Schlaug, 2003; Nigmatullina et al, 2015; Sluming et al, 2002). Furthermore, VBM studies (Hyde et al, 2006; Mandell et al, 2007) have examined co-variation of gray matter volume with participant performance on a musical assessment test (Peretz et al, 2003) to identify candidate brain regions that are related to the phenotypic expression of congenital amusia or tone-deafness (a pitch perception deficit, Vuvan et al, 2017). …”
Section: Introductionmentioning
confidence: 99%
“…The high scores achieved in all three groups suggest that the distinctions in music tested in the cMBEA are fairly easy for children with normal hearing. Similarly, Vuvan et al (2018) found that 175 participants aged 16 to 69 years (mean = 29.7 years) with no reported deficits often achieved maximum scores on this test (Vuvan et al, 2018). A slight decrease in score was only found in the Scale subtest and, again, this was a consistent finding across the three groups, confirming that the modified version of the cMBEA had little effect on abilities to detect musical differences in children with normal hearing.…”
Section: Modifications To the Child Mbea Do Not Affect Discriminationmentioning
confidence: 62%
“…Clearly, discrimination scores are reduced relative to normal hearing peers in all 4 of the CI groups. As discussed in previous papers, many children using CIs are effectively amusic (Hopyan et al, 2012;Polonenko et al, 2017;Lima et al, 2018) based on score cutoffs of ∼75% (Vuvan et al, 2018). Yet, unlike individuals with amusia, individuals with hearing loss who use CIs report frequent engagement with music and that they enjoy listening to music (Mirza et al, 2003;Migirov et al, 2009;Looi et al, 2012).…”
Section: The Modified Cmbea Does Not Yield Better Music Perception Scmentioning
confidence: 98%
See 1 more Smart Citation
“…We used the Montreal Battery for the Evaluation of Amusia (MBEA; [ 10 ]) to screen participants for amusia. Participants who scored 2 SD below the mean of the general population mean were classified as amusic [ 10 , 37 40 ]. Table 2 showed the mean score and standard deviation on the scale, contour, interval, rhythm, metric, and memory subtests of the MBEA for the amusic and control groups as well as the global score.…”
Section: Methodsmentioning
confidence: 99%